Resilience Meets Sustainable and Spiritual Background Into an Initial Review for the New Normal After the COVID-19 Pandemic - Bella, Ricardo Luiz Fernandes; Barboza, Douglas Vieira; Quelhas, Osvaldo Luiz Gonçalves; Meiriño, Marcelo Jasmim; França, Sergio Luiz Braga (Frontiers in Sustainability, 2021)
Objective: This work aims to generate an initial basis for a discussion of the strategic structuring of values that impact the perspective of planning at its different levels within the scope of organizational human relations. The value highlighted in this article is an intersection between organizational resilience and spirituality at work, through which production systems can maintain internal quality even after conforming to external pressures from the environment and moving towards sustainability. Design/methodology/approach: The methodology applied in this research consists of consulting and organizing a previous knowledge base of a research and development group in technology and sustainability. This knowledge base is based on research, articles, and books on sustainability and corporate responsibility. Then, this more sedimented knowledge base finds the most recent construction of the concept of spirituality in the workplace for the topic of interest from a triangulation of the concept of resilience, corporate sustainability, and spirituality at work. Results: The main findings of this research, if in the reflections on the impact of attribute resilience in the development and maintenance of productive systems. The main issue observed is the correspondence of the identity of the human being with identity, enabling the production of a predictable planning environment in the aspects of motivation and engagement to overcome moments of crisis. Originality/value: The originality of the article involves the construction of an abstract approach system to understand an attribute that, according to the literature, can be developed and articulated to achieve a perennial organizational performance in society.